Reframing participation through empowerment: Mechanisms driving Chinese women’s intentions in adventure sports tourism - Wenhao Guo; Yuanji Zhong; Yongshun Wang; Pengwei Chen; Shiqi Zhuang; Jingjin Liu (PLoS ONE, 2026)
Women’s participation in adventure sports tourism is growing in China but remains uneven under collectivist traditions and gendered expectations. Drawing on Self-Determination Theory and Empowerment Theory, this study examines how intrinsic and extrinsic motivations are associated with participation intentions, mediated by psychological, social, and political empowerment, and moderated by perceived risk. Survey data were collected from 566 women participating in skiing, surfing, and rock climbing at representative destinations. Standardized measures were employed, and moderated mediation analysis with bias-corrected bootstrapping was conducted to assess the hypothesized associations. Results reveal that intrinsic and extrinsic motivations positively predict participation intention via distinct empowerment pathways. While intrinsic motivation acts through psychological and political dimensions, extrinsic motivation engages all three, with political empowerment exerting the strongest mediation effect. Notably, risk perception significantly attenuates these indirect relationships. A key theoretical contribution is the reconceptualization of political empowerment: rather than resistance, it functions as a means of securing institutional legitimacy, proving resilient under elevated risk perception compared to the vulnerability of social empowerment. The study concludes with practical strategies for enhancing political legitimacy and risk management to promote sustained engagement.